2000
DOI: 10.1021/om990650f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Organic and Organometallic Functionalization on [1,5]-Silicon Shifts in Indenylsilanes

Abstract: Indenylsilanes bearing organic and organometallic substituents have been prepared in order to probe the effect of substitution on the rate of [1,5]-silicon shifts in this class of compounds. In an attempt to prepare 1,1,3-tris(trimethylsilyl)indene ( 7), the hitherto unknown silicon-functionalized bis(trimethylsilyl)dibenzo[a,d]fulvalene (9) was unexpectedly generated; this species was characterized by use of both NMR spectroscopy and X-ray crystallography and was rationally prepared in 68% yield from 3,3′-bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…A similar result was observed by Okuda and co-workers, who reported an oxidative coupling of a trimethylsilyl-substituted cyclopentadienide anion by iron(III) chloride . Stradiotto et al recently observed an oxidative coupling in the study of [1,5]-silicon shifts in indenylsilanes leading to isolation and characterization of the dimer [C 18 H 10 (SiMe 3 ) 2 ] 2 …”
Section: Resultssupporting
confidence: 80%
“…A similar result was observed by Okuda and co-workers, who reported an oxidative coupling of a trimethylsilyl-substituted cyclopentadienide anion by iron(III) chloride . Stradiotto et al recently observed an oxidative coupling in the study of [1,5]-silicon shifts in indenylsilanes leading to isolation and characterization of the dimer [C 18 H 10 (SiMe 3 ) 2 ] 2 …”
Section: Resultssupporting
confidence: 80%
“…[22] The reductive elimination from a Ni IV intermediate (step c) is also quite reasonable, as is the rearrangement of the initially formed 1-phenyl-1,3-bis(trimethysilyl)indene to the observed 3-phenyl-1,3-bis(trimethysilyl)indene isomer by a silyl migration (step e). [23] Finally, comproportionation of Ni II and Ni 0 species to give Ni I dimers (step d) has been reported, [24] although the origin of the putative "Ni 0 (PPh 3 ) 2 " fragment is not known at this point.…”
mentioning
confidence: 99%
“…Interaction between D / D′ and in situ generated carbodiimide affords F . 1,5-Sigmatropic rearrangement over the indenyl ring followed by an intramolecular proton shift gives the final product 11a…”
Section: Resultsmentioning
confidence: 99%